Efeitos diretos e indiretos da piscivoria de aves aquáticas e peixes na estrutura de uma assembleia modelo de peixes nativos e não nativos. - Silva, João Carlos Barbosa da (2015)
Indirect effects has larger consequences than direct effects in food webs, or at least comparable. The indirect effects are related with modifications in functional traits, such morphology, and habitat use and behavioral. The control of the access of waterbirds was provided by an iron net. Two piscivorous fishes were used: the native Hoplias aff. malabaricus and the non-native Hoplerythrinus unitaeniatus; the prey species were: Aphyocharax sp. (75 individuals), Moenkhausia forestii (75 individuals), Astyanax altiparanae (18 individuals) and Gymnotus inaequilabiatus (15 individuals). During the seven days of the experiment, five waterbirds species were registered around the lakes: Ardea cocoi, Syrigma sibilatrix, Egretta thula, Vanellus chilensis and Sterna superciliaris; we also registered A. cocoi and E. thula capturing fishes. Non-native piscivorous fish had significantly higher consumption rates than the native piscivore, independent on waterbirds access. Native piscivorous fishes presented reduced prey consumption and changed prey preference due to the indirect effects of waterbirds. For example, H. aff. malabaricus (native) consumed Aphyocharax sp., G. inaequilabiatus and A. altiparanae in lakes were waterbirds had no access, but preferentially consumed G. inaequilabiatus and reduced consumption of A. altiparanae and M. forestii in the lakes were waterbirds had access. The higher consumption of G. inaequilabiatus was related to the higher possibility of encounters when both were hiding from birds under aquatic macrophytes. In the results of two experiments which evaluated the effect of the predator origin (native and non-native) on a mounted prey assemblage (Aphyocharax sp. (75 individuals), Moenkhausia forestii (75 individuals), Astyanax altiparanae (18 individuals) e Gymnotus inaequilabiatus (15 individuals)), comparing species mortality in the lakes, controlling the access of waterbirds. The native species was H. aff. malabaricus and the non-native species was Astronotus crassipinnis. In the treatments with the native predators, the mortality was 19 %, and to non-native predator, the overall mortality was 33 %. In relation to prey preferences, A. crassipinnis selected the most abundant and small sized preys Aphyocharax sp. and M. forestii. On the other hand, H. aff. malabaricus preferred G. inaequilabiatus. There was a significant difference in prey mortality between predators and it may be related to ecomorphological features. Thus a second experiment was conducted to evaluate the mortality of prey based in multiple predator systems (Surubim lima, Pseudoplatystoma corruscans, H. aff. malabaricus and Astronotus crassipinnis) with distinct ecomorphological distances among them (functional traits). The ecomorphological distance between predators had no effect on prey mortality. Average mortality was higher in treatments with morphologically related predators (Sorubim lima and Pseudoplatystoma corruscans). Therefore, the consumption presented by A. crassipinnis was not related to the ecomorphological characteristics, but appears more related to its behavior and consumption of the most abundant preys. In summary, the results of the first experiment contributed to the understanding of the mechanisms involved in the role of multiple predators, including aquatic and semi-aquatic (waterbirds) organisms. The indirect effect of waterbirds in the food web was related to the origin of the predator (native or non-native). In the second experiment, due to the feeding plasticity and boldness behavior of A. crassipinnis, this non-native fish species has great potential to be a high impacting invasive species, especially for small prey fish in the upper Paraná River floodplain and elsewhere were it was or will be introduced. This aspect is potentially related to behavioral attributes, since the ecomorphology had no effect in prey mortality.